Mengapa Content Marketing itu Penting untuk Bisnis? - Oliver Richardo Saragi; Muhammad Fikriansah; Lewi Ebenezer Hasugian (AGUSPATI RESEARCH INSTITUTA, 2023)
This report aims to enhance the public’s understanding of the relevance of Content Marketing in business development. Through a descriptive qualitative approach, this study gathered data from the insights shared by Astri Soeparyono on the Bukalapak Youtube channel titled “Why is Content Marketing Important for Business?”. The analysis reveals that Content Marketing is an essential element often overlooked by business practitioners due to their inability to grasp its concept. Altough many believe that business promotion requires substaintial funds, with the right Content Marketing strategy, especially by leveraging social media, promotional costs can be minimized. Therefore, business professionals need to broaden their knowladge and skills in this areato optimize existing market potential. Adequate knowladge of Content Marketing can not only boost business visibility but also foster better relationships with customers.